The Differences of Pepsinogen I and H. Pylori Levels in Patients With Gastric Premalignant Lesion - Lubis, Ainun; Siregar, Gontar Alamsyah (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2022)
Background: Gastric cancer is the fifth most common cancer worldwide, precancerous lesions is triggered by H. pylori infection and any other factors. Recent reports confirmed that serum pepsinogens are a valuable biomarker gastric cancer even before the discovery of H. pylori. Research Methods: This study is a cross-sectional study involving 80 confirmed patients with Gastric Premalignant Lesion at Adam Malik General Hospital, Permata Bunda General Hospital, Medan, on April-November 2018. These two variables is sought using the Mann Whitney test (normality test P < 0,05). H. pylori were diagnosed by positive result of examination of Carbon-14 urea breath test (C-UBT) or Campylobacter-like organism (CLO). Examination of Pepsinogen I measured by Abbott ARCHITECT Pepsinogen I Reagent Kit (Abbott Laboratories Inc., Chicago, IL, USA). Result: Of the 60 participants who confirmed has gastritis premalignant lesion according to the inclusion criteria. From the table of characteristic descriptive, it was found that 48 patients were male (60%) and 32 patients were female (40%). From CLO and 14C-UBT, it was found 35 patients were H. pylori-positive (43,8%) and 45 patients were H. pylori-negative (56,3%). Mean age was 51.03 ± 10.97  years. Mean levels of Pepsinogen I  was 44.28 ± 21.77. From the second table, it was found that 35 (43,8%) patients  with H. pylori-positive has 47.84 mean levels of Pepsinogen I, and 45 (56,3%) patients with H. pylori-negative has 34,79 mean levels of Pepsinogen I. The results of Mann Whitney's correlation analysis found a significant correlation between Pepsinogen (PG) I and H. Pylori in patients with Gastric Premalignant Lesion (p < 0,05). Conclusion : It was found that there was a correlation between Pepsinogen (PG) I levels and H. Pylori in patients with Gastric Premalignant Lesion (p < 0,05).